(untitled) (Sebha University Conference Proceedings, 2022)
Corruption is a dangerous and widespread global phenomenon with deep roots, taking wide dimensions. Various factors are difficult to distinguish, and the degree of their comprehensiveness varies from one society to another. Its methods and manifestations with the development of modern life, and the increase in its requirements turned corruption to be a prevailing culture with the increase of human passion and unbridled desire to obtain spoils, privileges and quick financial gain. This is happening regardless of the means a person uses, whether legal or illegal. Its pace has increased at present in an unprecedented way. For example, corruption affected individuals, groups, institutions, and even state entities and policies, and inflicted heavy human and material losses on them. In this research, we address the disclosure of the social factors leading to the spread of a culture of coexistence with corruption in government institutions. This research then discusses the current and future effects on society and the state. This research falls under the descriptive analytical approach. The most important results of the research concluded that the most significant social factors leading to the spread of a culture of coexistence with corruption in government institutions are: the weakness of the institutions of social control, the fragility of the state, the weakness of national affiliation, the change of values and morals, and the change in the process of education and socialization. The most important current effects and the future for the spread of this culture on society and the state are economic deterioration. However, as a result, social problems at the family and community levels are spread, the collapse and loss of the prestige of the state of law and institutions increase, weakening of citizen confidence in state institutions and officials diminishes, and also the weak turnout of citizens for political participation.